Adjuvant capecitabine plus bevacizumab versus capecitabine alone in patients with colorectal cancer (QUASAR 2): an open-label, randomised phase 3 trial - Love, S; Kerr, R; Segelov, E; Johnstone, E; Falcon, B; Hewett, P; Weaver, A; Church, D; Scudder, C; Pearson, S; Julier, P; Pezzella, F; et al. (Lancet, 2016)
Background Anti-angiogenic agents have an established role in the treatment of metastatic colorectal cancer (CRC). It was hypothesised that their effectiveness may be augmented in earlier stage disease with a more malleable vasculature. The QUASAR 2 trial examined whether bevacizumab could improve disease-free survival (DFS) when added to single agent capecitabine in the adjuvant setting of colorectal cancer (registration ISRCTN 4513315). Methods Patients aged 18 or over with WHO Performance Status 0 or 1 from 170 centres across 6 countries, who had undergone potentially-curative surgery for histologically proven stage III/ high risk stage II CRC, were randomly assigned (1:1 ratio, non-blinded, minimisation with a random element stratified by age, stage, tumour subsite and country) to receive capecitabine alone (CAP), comprising a 3-week cycle of 1250mg/m2 twice daily for 14 days followed by a 7 day break for a total of 8 cycles, or the same in combination with bevacizumab, 75mg/kg intravenous infusion over 90 minutes on day 1 of each 3-week cycle (CAPBEV). The primary end-point was 3-year disease-free survival (DFS) with overall survival (OS) a secondary endpoint. Both of these were intention-to-treat analyses. A comparative analysis of toxicity included only patients who received at least one dose of their randomised treatment. Tumour tissue was used for DNA and vascular exploratory biomarker analysis. Findings The final results of the QUASAR2 trial are presented here. 1952 patients were entered onto the study between April 2005 and October 2010, with 1941 evaluable (968 CAP and 973 CAPBEV). Median follow-up was 492 years (95% CI 4.87-4.96). Overall, no significant difference was seen in 3-year DFS (primary endpoint) between CAPBEV (754%) and CAP (784%) (hazard ratio (HR) 106; 95% CI 089-125; p=054). Of 1922 patients analysed for toxicity, the most common grade 3 / 4 adverse events were hand foot syndrome (n=201 for CAP and n=257 for CAPBEV) and diarrhoea (n=102 for CAP and n=104 for CAPBEV). An expected increase in all-grade hypertension (n=320 versus 75), proteinuria (n=197 versus 49) and wound healing problems (n=30 versus 17) was observed with the addition of bevacizumab to capecitabine. 571 SAEs were reported (221 with CAP and 350 with CAPBEV). Interpretation This study shows that the addition of bevacizumab to capecitabine adjuvant therapy in CRC does not produce benefit in this patient population when considered as a whole and that it should not be used.